Antibody free ELISA-like assay for the detection of transcription factors based on double-stranded DNA thermostability. Issue 9 (27th March 2020) - Sun, Yue; Li, Zhiyan; Lau, Choiwan; Lu, Jianzhong
Abstract : Transcription factors (TFs) play critical roles in gene expression regulation and disease development. Herein we report a chemiluminescence assay for the detection of transcription factor based on double-stranded DNA thermostability. Abstract : Transcription factors (TFs) play critical roles in gene expression regulation and disease development. In this paper, we report an antibody free ELISA-like assay which could be used to analyze transcription factor NF-κB p50 with comparatively low cost and high throughput. This assay is based on the stabilization of a duplex DNA probe by binding with a transcription factor. The double-stranded DNA (dsDNA) probe immobilized on a 96-well plate was too short in length to stabilize its duplex structure at a relatively high temperature and would unwind into a single strand. In the presence of a target TF, the protein bound to a specific TF-binding site and prevented the specific dsDNA probe from being unzipped at the washing temperature, thus holding the chemiluminescence signal. This method could sensitively detect NF-κB p50 with a detection limit of 0.5 nM. The proposed strategy provides a convenient, cheap and high throughput detection method of TFs, which can potentially help the development of drug discovery and disease diagnosis.